ChemInform Abstract: A Practical and Efficient Synthesis of 6‐Carboalkoxy‐13‐cycloalkyl‐5H‐indolo[2, 1‐a] [2]benzazepine‐10‐carboxylic Acid Derivatives. Issue 28 (15th July 2014) - Hewawasam, Piyasena; Tu, Yong; Hudyma, Thomas W.; Zhang, Xiaofan; Gentles, Robert G.; Kadow, John F.; Meanwell, Nicholas A.
Abstract A new synthesis of benzazepine derivatives from hemiaminals is described.